Mutational analysis of Peroxiredoxin IV: exclusion of a positional candidate for multinodular goitre - Bonifazi Emanuela; Filetti Sebastiano; Arturi Franco; Amati Francesca; D'Apice M Rosaria; Capon Francesca; Giardina Emiliano; Pucci Sabina; Conte Chiara; Novelli Giuseppe (BMC, 2002)
Abstract Background Multinodular goitre (MNG) is a common disorder characterised by an enlargement of the thyroid, occurring as a compensatory response to hormonogenesis impairment. The incidence of MNG is dependent on sex (female:male ratio 5:1) and several reports have documented a genetic basis for the disease. Last year we mapped a MNG locus to chromosome Xp22 in a region containing the peroxiredoxin IV (Prx-IV) gene. Since Prx-IV is involved in the removal of H2O2 in thyroid cells, we hypothesize that mutations in Prx-IV gene are involved in pathogenesis of MNG. Methods Four individuals (2 affected, 2 unrelated unaffected) were sequenced using automated methods. All individuals were originated from the original three-generation Italian family described in previous studies. A Southern blot analysis using a Prx-IV full-length cDNA as a probe was performed in order to exclude genomic rearrangements and/or intronic mutations. In addition a RT-PCR of PRX-IV was performed in order to investigate expression alterations. Results No causative mutations were found. Two adjacent nucleotide substitutions were detected within introns 1 and 4. These changes were also detected in unaffected individuals, suggesting that they were innocuous polymorphisms. No gross genomic rearrangements and/or restriction fragment alterations were observed on Southern analysis. Finally, using RT-PCR from tissue-specific RNA, no differences of PRX-IV expression-levels were detected between affected and unaffected samples. Conclusions Based on sequence and genomic analysis, Prx-IV is very unlikely to be the MNG2 gene.